Channel slope: an index of watershed characteristics - Chen, Ming, author; Schleusener, Richard A., author; Colorado State University, publisher (Colorado State University. Libraries, 1960)
Channel slope is related to unit discharge in eastern Colorado and western Nebraska. Channel slope can be estimated from parameters of area, drainage density, infiltration, location and precipitation. Measurements of these watershed characteristics can be used to estimate the similarity of physical and runoff characteristics between watersheds.
CER60MCC37.
Submitted for publication in The Journal of Geophysical Research, The American Geophysical Union.
Keywords: Watersheds -- Colorado -- Measurement; Watershed management -- Colorado; Stream measurements -- Colorado; Watersheds -- Nebraska -- Measurement; Watershed management -- Nebraska; Stream measurements -- Nebraska